Association of Osteogenesis Imperfecta with Pre-eruptive Resorption: Two Cases - Rutbil, Melek (2026)
Osteogenesis imperfecta (OI) is a rare hereditary disorder of the connective tissue, characterized by bone fragility and associated craniofacial and dental abnormalities. Pre-eruptive intracoronal resorption (PIR) is an uncommon developmental anomaly that affects unerupted teeth, typically presenting as asymptomatic radiolucent lesions within the coronal dentin. Although both conditions have been individually described in the literature, their coexistence has not been previously reported. This case report describes two male patients, aged 45 and 51 years, both diagnosed with OI and found to have PIR in multiple impacted teeth. In the first case, panoramic radiographs revealed radiolucent lesions within the crowns of impacted teeth #13 and #33, which were further characterized by cone-beam computed tomography (CBCT) as PIR involving enamel and dentin. In the second case, panoramic imaging demonstrated PIR in impacted teeth #37, #38, and #48, confirmed by CBCT as extensive intracoronal defects adjacent to the mandibular canal. Both patients were referred for surgical evaluation following radiographic diagnosis. This report highlights the potential coexistence of OI and PIR, raising questions about possible shared pathogenic mechanisms. More importantly, the cases emphasize the role of radiographic evaluation in early diagnosis.